Protein-altering and regulatory genetic variants near GATA4 implicated in bicuspid aortic valve - Yang, Bo; Zhou, Wei; Jiao, Jiao; Nielsen, Jonas B.; Mathis, Michael R.; Heydarpour, Mahyar; Lettre, Guillaume; Folkersen, Lasse; Prakash, Siddharth; Schurmann, Claudia; Fritsche, Lars; Farnum, Gregory A.; et al. (Nature communications, 2017)
Bicuspid aortic valve (BAV) is a heritable congenital heart defect and an important risk factor for valvulopathy and aortopathy. Here we report a genome-wide association scan of 466 BAV cases and 4,660 age, sex and ethnicity-matched controls with replication in up to 1,326 cases and 8,103 controls. We identify association with a noncoding variant 151 kb from the gene encoding the cardiac-specific transcription factor, GATA4, and near-significance for p.Ser377Gly in GATA4 . GATA4 was interrupted by CRISPR-Cas9 in induced pluripotent stem cells from healthy donors. The disruption of GATA4 significantly impaired the transition from endothelial cells into mesenchymal cells, a critical step in heart valve development. Bicuspid aortic valve (BAV) is the most common human congenital cardiovascular malformation. Here, the authors perform a genome-wide association study for BAV and identify risk variants in the gene region of cardiac-specific transcription factor GATA4 and implicate GATA4 in heart valve development.